Navigating materiality in sustainability reporting: A scoping review of single and double materiality approaches - Mohamed Anas Belidan; Halima Baghad (Zeszyty Teoretyczne Rachunkowości)
Purpose: The purpose of this analysis is to examine the theoretical foundations of materiality research within sustainability reporting, the current state of research and the legitimacy of different approaches, and to compare between different normalizations and frameworks. Methodology/approach: Employing a content analysis approach, this study used a scoping review. Over 86 related papers were analyzed. Data were extracted from Scopus and Google Scholar on April 22, 2024. Findings: Our review reveals the growing importance of double materiality in sustainability reporting research, driven by stakeholders’ expectations and regulatory demands. Theoretical frameworks like stakeholder and legitimacy theory help explain the complexities in materiality assessments, while inconsistent standards highlight the need for harmonization. We emphasize the critical role of stakeholder engagement and call for further research on standardization, sector-specific challenges, and the implementation of double materiality. Research limitations: This article has certain limitations. Methodologically, it uses a limited set of search keywords. Regarding the findings, this study shows a scarcity of papers on materiality in sustainability reporting. Practical implications: This study aims to provide managers and public policymakers with insight into the degree to which materiality and double materiality are incorporated into essential elements of organizations, such as governance, stakeholder requirements, and social impact evaluations. Originality/value: As of the date this article was written, and to the extent of our knowledge, there are no existing research papers specifically using a scoping review on materiality assessment within this scope.